Republic of Croatia : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Croatia's economic vulnerability is discussed in this study. Using the balance sheet approach (BSA), this paper analyzes Croatia's overall and sectoral vulnerabilities. Croatia's financial sector balance sheet is exposed to liquidity, contagion, and currency risks. With strong pre-crisis prudential policies and parent banks' willingness to keep or even increase exposures, the economy's capacity to tackle another major macroeconomic or financial shock is limited. Given the stable exchange rate policy, a consistent set of structural, fiscal, monetary, and prudential policies are needed for sustained growth and reduced vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet